2017
DOI: 10.1111/jems.12233
|View full text |Cite
|
Sign up to set email alerts
|

The burden of glory: Competing for nonmonetary incentives in rank‐order tournaments

Abstract: In an environment in which elite, highly paid professionals compete for nonmonetary rewards, we find evidence of underperformance. Our analysis suggests that choking under pressure from high-stakes nonmonetary rewards is behind the underperformance. This implies that high stakes nonmonetary rewards can create meaningful pressure on individuals and lead to worse performance, a distinct issue that has yet to be adequately examined. These findings come from an examination of the behavior of top U.S. golfers compe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 71 publications
(100 reference statements)
1
8
0
Order By: Relevance
“…Our estimates for these joint effects are precise and mostly small (less than 0.1 strokes) for round-level effects. However, the joint effect for all of Round 3 starting with a tournament score substantially above or below par is around 0.2 strokes, which is similar to the round-level effects found by PS, Brown (2011), and Kali, Pastoriza, and Plante (2015).…”
supporting
confidence: 59%
See 2 more Smart Citations
“…Our estimates for these joint effects are precise and mostly small (less than 0.1 strokes) for round-level effects. However, the joint effect for all of Round 3 starting with a tournament score substantially above or below par is around 0.2 strokes, which is similar to the round-level effects found by PS, Brown (2011), and Kali, Pastoriza, and Plante (2015).…”
supporting
confidence: 59%
“…By comparison, the mean round-level effects found by Brown (2011) and Kali, Pastoriza, and Plante (2015) were both around 0.2 strokes, and PS's estimate was 0.25 strokes per round. Our estimates are in the same ballpark (somewhat smaller for round effects but larger, per hole, for half-round effects).…”
Section: Table 12]mentioning
confidence: 99%
See 1 more Smart Citation
“…Within the study of golf, for example, Hickman and Metz (2015) analyze how the amount of money riding on a particular putt impacts the likelihood that putt is made. Kali, Pastoriza, and Plante (2018) study tournament round scores and find that nonmonetary incentives (Ryder Cup qualifying points) impact performance in an adverse manner. Brown (2011) finds that playing in a tournament with superstars can also cause performance to decline.…”
mentioning
confidence: 99%
“…Using tennis data, Cohen-Zada et al (2017) found that males choke consistently under pressure and to a larger extent than females. 1 Interestingly, recent evidence has also shown that people may choke even under the pressure of non-monetary incentives (Kali et al (2017)).…”
mentioning
confidence: 99%